Імітацыі заходнееўрапейскіх дэнарыяў Х-ХІ стст. са збораў Нацыянальнага гістарычнага музея Рэспублікі Беларусь - Крыцук, Р. І. (Полоцкий государственный университет, 2018)
IMITATIONS OF WESTERN DENARIA OF THE X-XI CENTURIES FROM ARCHIVES OF THE NATIONAL HISTORICAL MUSEUM OF BELARUS R. KRYTSUK В период 2015-2016 годов в собрание Национального исторического музея Республики Беларусь были переданы две имитации европейских денариев Х-ХІ веков. Первая монета найдена летом 2015 года, в г. Полоцк в реке Двине. Она является имитацией неустановленного денария с территории Польши или Германии. Спектральный анализ монеты следующий: Cu - 35.63%; Sn - 25.01%; Zn - 19.89%; Au - 4.51%; Ag-8.67% Pb - 1.35%. Вторая монета найдена в 2016 году в окрестностях д. Веснино Логойского р-на Минской обл. Это имитация денария г. Доккум (совр. Нидерланды) графа Бруно III (1050-1057, Dokkum, gr. Bruno III, Dbg. 501). Спектральный анализ монеты следующий: - Cu - 76.75%, Pb - 9.49%, Sn - 6.87%, Zn - 6.25%, Ag - 0.64%. Обе имитации использовались в качестве украшений-подвесок.=In the period 2015-2016 two imitations of European denarii of the 10th-11th centuries were transferred to the National Historical Museum of the Republic of Belarus. The first coin was found in the summer of 2015, in Połack in the Dvina River. It probably imitates a denarius from the territory of Poland or Germany. Also, it is a workpiece for suspension. The spectral composition of the coin is as follows: Cu - 35.63%; Sn - 25.01%; Zn - 19.89%; Au - 4.51%; Ag - 8.67% Pb - 1.35%. The second coin was found in 2016, near the village of Vesninа, Lahoysk district of the Minsk region. This is an imitation of the denarius of the city of Dokkum, the Fristly Count of Bruno III (1050-1057, Dokkum, gr. Bruno III, Dbg. 501). The coin was used as a pendant. The chemical composition of the coin is as follows: - Cu - 76.75%, Pb - 9.49%, Sn - 6.87%, Zn - 6.25%, Ag - 0.64%. It is likely that both coins were made for use as decoration.